New Cardiodactylus species from unsuspected places in Southeast Asia (Orthoptera, Grylloidea, Eneopterinae) - Robillard, Tony (Zootaxa, 2011)
Two new species of Cardiodactylus crickets are described from unsuspected places in Southeast Asia: C. singapura n. sp., from within the island-city of Singapore, and C. thailandia n. sp. from Thailand. Descriptions focus on male and female genitalia, forewing venation and coloration. Data are provided for C. singapura n. sp. fine-scaled habitat and calling song. Consequences in terms of distribution of the genus and conservation are discussed.